Tuning the confinement potential between spinons in the Ising chain CoNb2O6 using longitudinal fields and quantitative determination of the microscopic Hamiltonian: data archive - Woodland, L; Macdougal, D; Cabrera, I M; Thompson, J D; Prabhakaran, D; Bewley, R I; Coldea, R (University of Oxford, 2023)
The deposited package contains experimental single crystal inelastic neutron scattering data probing the spin dynamics in the quantum Ising chain magnet CoNb2O6 in longitudinal magnetic field together with corresponding theoretical calculations of the spin dynamics. A matlab script to read and plot all data in ASCII files is also supplied.